2005
DOI: 10.1124/jpet.105.088336
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Akt and Mitogen-Activated Protein Kinase Systems in the Protective Effect of Poly(ADP-Ribose) Polymerase Inhibition in Langendorff Perfused and in Isoproterenol-Damaged Rat Hearts

Abstract: Blocking poly(ADP-ribosyl)ation of nuclear proteins protects the heart from ischemia-reperfusion injury. In addition, activation of Akt and mitogen-activated protein kinase (MAPK) cascades also plays a pivotal role in the survival of cardiomyocytes during ischemia-reperfusion; however, the potential interplay between these pathways is yet to be elucidated. We therefore tested the hypothesis whether poly(ADP-ribose) polymerase (PARP) inhibition can modulate Akt and MAPK signaling of ischemic-reperfused rat hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…The first indication is from inhibitor studies, which demonstrated that several different nonspecific PARP inhibitors could enhance the endotoxin-induced or ischemia-reperfusion-induced activation of phosphatidylinositol 3-kinase (PI-3-kinase)/AKT/PKB, extracellular signal-regulated kinase 1/2, and p38 mitogen-activated protein kinase in ex vivo models. The rapid activation of the JNK-1 cascade was blocked in the presence of nonspecific PARP inhibitors (310,423,424). As mentioned above, a recent report provided indirect evidence that activation of JNK-1 is required for PARP-1-dependent mitochondrial dysfunction, AIF translocation, and subsequent cell death (443).…”
Section: Adp-ribosylation Reactions In Cell Death Processesmentioning
confidence: 92%
See 1 more Smart Citation
“…The first indication is from inhibitor studies, which demonstrated that several different nonspecific PARP inhibitors could enhance the endotoxin-induced or ischemia-reperfusion-induced activation of phosphatidylinositol 3-kinase (PI-3-kinase)/AKT/PKB, extracellular signal-regulated kinase 1/2, and p38 mitogen-activated protein kinase in ex vivo models. The rapid activation of the JNK-1 cascade was blocked in the presence of nonspecific PARP inhibitors (310,423,424). As mentioned above, a recent report provided indirect evidence that activation of JNK-1 is required for PARP-1-dependent mitochondrial dysfunction, AIF translocation, and subsequent cell death (443).…”
Section: Adp-ribosylation Reactions In Cell Death Processesmentioning
confidence: 92%
“…Several recent studies indicate that PARP-1-catalyzed poly-ADP-ribosylations may affect signaling pathways through negative or positive modulation of distinct kinase activities, which play a significant role in cell survival and cell death (310,399,423,424). The first indication is from inhibitor studies, which demonstrated that several different nonspecific PARP inhibitors could enhance the endotoxin-induced or ischemia-reperfusion-induced activation of phosphatidylinositol 3-kinase (PI-3-kinase)/AKT/PKB, extracellular signal-regulated kinase 1/2, and p38 mitogen-activated protein kinase in ex vivo models.…”
Section: Adp-ribosylation Reactions In Cell Death Processesmentioning
confidence: 99%
“…Recent studies using PARP inhibitors suggest that poly(ADP-ribosyl)ation may affect signaling pathways which are linked to cell survival [25,26]. To better understand the implication of PARP-1 activation in cell death, we analyzed the effect of PAR synthesis on the MEK/ERK signaling pathway in HeLa cells exposed to the alkylating agent N-methyl-N 0 -methyl-nitro-N-nitrosoguanidine (MNNG).…”
Section: Introductionmentioning
confidence: 99%
“…PARP inhibitors show pronounced protection against myocardial ischemia (16), neuronal ischemia (17,18), acute lung inflammation (19), acute septic shock (20), zymogen-induced multiple organ failure (21), and diabetic pancreatic damage (22)(23)(24), providing evidence for the role of excessive PARP-1 activation in cell death. It is believed that by preventing excessive NAD ϩ and ATP utilization, PARP inhibitors protect cells against oxidative damage, but some recent data suggest a more complex mechanism for the cytoprotection (25,26). There is evidence that PARP activation can contribute to exaggeration of mitochondrial damage (27) and mitochondrial reactive oxygen species production (28), indicating that PARP activation can modulate processes outside of the nucleus.…”
mentioning
confidence: 99%